Effect of an Educational Intervention Based on Self-efficacy Theory and Health Literacy Strategies on Pregnancy Outcomes: A Randomized Clinical Trial - Seyedeh Sara Kharazi; Nooshin Peyman; Habibolah Esmaily (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2018)
Introduction:Maternal health literacy during pregnancy can refer to the socio-cognitive skills, which determine the motivation and ability of mothers to understand and use beneficial information in order to maintain and promote health of themselves and their children. The present study aimed to determine the effects of an educational program based on self-efficacy theory and health literacy strategies on pregnancy outcomes at healthcare centers affiliated to Mashhad University of Medical Sciences, Mashhad, Iran. Methods: This randomized clinical trial was performed on 76 pregnant women, who referred to the healthcare centers of Mashhad for routine pregnancy period checkups in 2015. The participants were assigned to the two groups of intervention and control. Data collection tools included a demographic questionnaire, maternal health literacy and pregnancy outcome questionnaire (MHLAPQ), and perceived dietary self-efficacy questionnaire. The questionnaires were completed by the participants, followed by implementation of the educational intervention for the test group according to a pilot study. Afterwards, the questionnaires were again completed immediately post-intervention, as well as within a three-month interval (follow-up). All the data were statistically analyzed by t-test, Chi-square, one-way analysis of variance (ANOVA), and repeated measures ANOVA using SPSS version 15. For all tests, P < 0.05 was considered as significant. Results: The findings of this study demonstrate that no significant difference was observed between the intervention and control groups in terms of maternal health literacy, self-efficacy, and pregnancy period cares pre-intervention (P>0.001). On the other hand, we reported a significant difference post-intervention regarding the mean scores of maternal health literacy and self-efficacy in the test group (P ≥ 0.001). Conclusion: According to the results of this study, the designed educational intervention based on self-efficacy theory might improve maternal health literacy and promote normal birth weight in newborns.